Accelerated Visualization of Dynamic Molecular Surfaces - Lindow, Norbert; Baum, Daniel; Prohaska, Steffen; Hege, Hans-Christian (Computer graphics forum, 2010)
Molecular surfaces play an important role in studying the interactions between molecules. Visualizing the dynamic behavior of molecules is particularly interesting to gain insights into a molecular system. Only recently it has become possible to interactively visualize dynamic molecular surfaces using ray casting techniques. In this paper, we show how to further accelerate the construction and the rendering of the solvent excluded surface (SES) and the molecular skin surface (MSS). We propose several improvements to reduce the update times for displaying these molecular surfaces. First, we adopt a parallel approximate Voronoi diagram algorithm to compute the MSS. This accelerates the MSS computation by more than one order of magnitude on a single core. Second, we demonstrate that the contour‐buildup algorithm is ideally suited for computing the SES due to its inherently parallel structure. For both parallel algorithms, we observe good scalability up to 8 cores and, thus, obtain interactive frame rates for molecular dynamics trajectories of up to twenty thousand atoms for the SES and up to a few thousand atoms for the MSS. Third, we reduce the rendering time for the SES using tight‐fitting bounding quadrangles as rasterization primitives. These primitives also accelerate the rendering of the MSS. With these improvements, the interactive visualization of the MSS of dynamic trajectories of a few thousand atoms becomes for the first time possible. Nevertheless, the SES remains a few times faster than the MSS.